1996
DOI: 10.1002/ana.410390316
|View full text |Cite
|
Sign up to set email alerts
|

Hypoplasia of the cerebellar vermis in neurogenetic syndromes

Abstract: There are conflicting reports on the relationship between cerebellar vermal lobule hypoplasia and autism. Using quantitative magnetic resonance image analysis, we measured the cerebellar vermis in 125 normal individuals with a broad age range and 102 patients with a variety of neurogenetic abnormalities. We conclude that hypoplasia of cerebellar vermal lobules VI and VII is a nonspecific finding that even occurs in several conditions with-out autistic behavior. This suggests that it is not a specific neuroanan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 8 publications
3
30
0
Order By: Relevance
“…A size reduction of the posterior vermis was not exclusively found in a subset of patients with autism, but also in a percentage of patients suffering from neurogenetic syndromes without autistiform features. 31 We studied here the neuroanatomy of a fragile X mouse model in living animals. The advantage of MRI recordings of living mice is that fixation artefacts are avoided and that the development of specific brain structures can be registered at several time points in the life of the same mouse.…”
Section: Discussionmentioning
confidence: 99%
“…A size reduction of the posterior vermis was not exclusively found in a subset of patients with autism, but also in a percentage of patients suffering from neurogenetic syndromes without autistiform features. 31 We studied here the neuroanatomy of a fragile X mouse model in living animals. The advantage of MRI recordings of living mice is that fixation artefacts are avoided and that the development of specific brain structures can be registered at several time points in the life of the same mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies of the cerebellum in autism have been inconsistent (Acosta & Pearl, 2004). Some researchers have found smaller cerebellar measurements, particularly in the vermis (Courchesne, 1991(Courchesne, , 1997(Courchesne, , 1999Courchesne et al, 2001;Courchesne et al, 1989;Courchesne et al, 1994Courchesne et al, , 1995Hashimoto et al, 1993;Murakami et al, 1989;Schaefer et al, 1996). One study found a significant increase in unadjusted cerebellar volume in autism, but the difference did not remain significant once total brain volume was controlled for (Herbert et al, 2003).…”
Section: Hb Cleavinger Et Almentioning
confidence: 99%
“…Similar to the L7En-2 phenotype, cerebella of ASD patients showed cell loss, abnormal neuronal differentiation, and incorrect wiring of the cerebellar cortex (Ritvo et al, 1986;Bauman and Kemper, 2005;Schaefer et al, 1996;Palmen et al, 2004;Tabuchi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%